Eugène Delacroix et ses violons d’Ingres - Kociubińska, Edyta (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
The paper is devoted to Eugène Delacroix, the greatest French Romantic painter, who combines the “external cold” and the “inner fire”, as described by René Huyghe. An analysis of selected fragments of his Journal brings to the fore Delacroix’s literary and musical passions and their influence on the artist’s painting.